A safe method for the retrieval of a dislocated trial head in total hip arthroplasty - Janipireddy, Satish B.; Sinha, Sanjay; Sinha, Sanjay; Ferguson, David W.; Ferguson, David W.; Atkinson, Henry D.; Atkinson, Henry D. (International Journal of Research in Medical Sciences, 2017)
Total hip arthroplasty is a life changing procedure providing a significant improvement in the quality of life for those receiving treatment. An 81-year-old male with severe right sided hip osteoarthritis underwent uncemented total hiparthroplasty. Intraoperatively the 32mm trial head dislodged from the trial stem over the anterior rim of the acetabulum relocating to within the pelvic cavity. Time efficient retrieval was performed during primary surgery through a mini-incision at the iliac crest.